Efektivitas Perbedaan Warna Tempat Sampah Sebagai Upaya Pemilahan Sampah di SDN 18 Bonto-Bonto, Kelurahan Balleangin, Kecamatan Balocci, Kabupaten Pangkep - Arbi Ahmadi; Anwar, Arif; Affifah Nisa Ul Ulmi Al-Daisi; Sophia Adiba S.Rauf; Fadliah Zaid; Dian Putri Ayu; Andi Besse Mutmainnah; Desweeta Aprilia La’lang (WISE Pendidikan Indonesia, 2025)
Background: Garbage is a remnant of human activities. In addition, waste is also divided according to its nature that is easy to decompose or not, namely organic and inorganic waste. Most of the people of Balleangin Lingkungan II (Padangtangalau) have not done proper waste processing. The waste is not sorted first and immediately burned. Therefore, an action is needed that can increase and change people's behavior in order to be able to process their own waste. Objective: To hold a color difference in the garbage can at SDN 18 Bonto-Bonto so that waste can be sorted in order to maintain the cleanliness of the school environment. Methods: In this intervention activity, education, educational games, and demonstrations were carried out for 4th and 5th grade students of SDN 18 Bonto-Bonto. Results: After counseling and demonstration, an increase in knowledge of 25.5% was obtained in 23 samples. As many as 82.6% of students obtained a post test score above 70, so it can be concluded that 82.6% of these students can understand the meaning and purpose of waste sorting.